Some toxic and enzymatic activities of Bothrops ammodytoides (yarará ñata) venom - de Roodt, Adolfo R. (2000)
Fil: de Roodt, Adolfo R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Producción de Biológicos; Argentina.